2015
DOI: 10.1016/j.comppsych.2015.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Examining the associations between emotion regulation difficulties, anxiety, and eating disorder severity among inpatients with anorexia nervosa

Abstract: Objective There is growing interest in the role of emotion regulation in anorexia nervosa (AN). Although anxiety is also hypothesized to impact symptoms of AN, little is known about how emotion regulation, anxiety, and eating disorder symptoms interact in AN. In this study, we examined the associations between emotion regulation, anxiety, and eating disorder symptom severity in AN. Methods Questionnaires and interviews assessing emotion regulation difficulties, anxiety, eating disorder symptoms, and eating d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 28 publications
2
21
0
1
Order By: Relevance
“…Interestingly, our findings also showed that difficulties in ER contribute unique variance, above and beyond BMI, age, depression, and anxiety, to both binge frequency and ED psychopathology. Specifically, greater difficulties in ER were associated with more frequent binge episodes-as has been reported in a nonclinical sample (Whiteside et al, 2007)-and greater ED psychopathology, consistent with research examining other EDs (Haynos, Roberto, & Attia, 2015;Woltz et al, 2015). However, this is one of the first studies to show these associations in individuals with BED.…”
Section: Discussionsupporting
confidence: 83%
“…Interestingly, our findings also showed that difficulties in ER contribute unique variance, above and beyond BMI, age, depression, and anxiety, to both binge frequency and ED psychopathology. Specifically, greater difficulties in ER were associated with more frequent binge episodes-as has been reported in a nonclinical sample (Whiteside et al, 2007)-and greater ED psychopathology, consistent with research examining other EDs (Haynos, Roberto, & Attia, 2015;Woltz et al, 2015). However, this is one of the first studies to show these associations in individuals with BED.…”
Section: Discussionsupporting
confidence: 83%
“…Emotion regulation difficulties are widely acknowledged in patients with EDs (Gianini et al, ; Haynos, Roberto, & Attia, ; Lavender et al, ; Wolz et al, ) with some studies also suggesting emotion dysregulation as a transdiagnostic risk factor for developing ED symptomatology (Brockmeyer et al, ; Svaldi, Griepenstroh, Tuschen‐Caffier, & Ehring, ). However, it is still unclear whether there are significant differences on how the different ED types regulate emotions (Brockmeyer et al, ; Danner et al, ) or whether they can be modified by current first‐line treatment.…”
Section: Discussionmentioning
confidence: 99%
“…ADHD and BPD often coexist (Matthies & Philipsen, 2014), and one longitudinal study showed that individuals with childhood ADHD are at a 13-fold increased risk for BPD in adolescence (Miller et al, 2008). ADHD and BPD are both characterized by emotional/affective instability and impulsive behavior (Matthies & Philipsen, 2014), which may lead to disordered eating behavior (Dawe & Loxton, 2004;Haynos et al, 2015). ADHD and BPD are both characterized by emotional/affective instability and impulsive behavior (Matthies & Philipsen, 2014), which may lead to disordered eating behavior (Dawe & Loxton, 2004;Haynos et al, 2015).…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%
“…On the other hand, women with BPD have been reported to have a higher likelihood of ED diagnosis than women without this condition (Reas, Rø, Karterud, Hummelen, & Pedersen, 2013). ADHD and BPD are both characterized by emotional/affective instability and impulsive behavior (Matthies & Philipsen, 2014), which may lead to disordered eating behavior (Dawe & Loxton, 2004;Haynos et al, 2015). In one study, the mood of women with high borderline personality traits was improved with food consumption, suggesting that individuals with this personality trait might be at a particularly high risk for subclinical ED (Ambwani & Morey, 2015).…”
Section: Interpretation Of the Findingsmentioning
confidence: 99%